Probiotics as Anti-Tumor Agents: Insights from Female Tumor Cell Culture Studies - Chiara Giorgi; Francesca Lombardi; Francesca Rosaria Augello; Ylli Alicka; Massimiliano Quintiliani; Skender Topi; Annamaria Cimini; Vanessa Castelli; Michele d’Angelo (Biomolecules)
Breast and ovarian cancers are among the most prevalent cancers in women. Cancerous cells are characterized by their ability to continuously cycle and migrate, forming metastases. Some probiotic strains have shown anti-tumorigenic effects. This study tested the impact of probiotics on OVCAR-3 and MDA-MB-231 cell lines by analyzing proteins involved in cell cycle regulation (pP53, Cyclin D1, pERK1), cell survival (AKT), and cell migration (RhoA) using Western blotting and scratch wound tests. Results indicated a reduction in these proteins and decreased cell migration velocity post-treatment. These findings suggest that certain probiotic combinations can arrest the cell cycle, promote cell death, and reduce cell migration, potentially serving as promising candidates alongside standard therapies.